Urgency Of Undergraduate Student Resilience To Mental Health: A Systematic Literatur Review - Aditia Kharisma Meliala; Ilfiandra (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Resilience is one of the important characteristics possessed by students, to be able to survive in difficult situations, succeed, and be happy in living life. The motivation behind this research is to see the relationship between student resilience and mental health. This study uses a systematic literature review (SLR) method taken from various international literature through Google Scholar, PubMed, publish and perish and Sciendirect using the keywords "resilience, mental health, and university students". This study found that there is a positive relationship between resilience and mental health. With resilience, students will be better prepared to deal with stress and adversity, overcome learning difficulties, anxiety disorders, PTSD (post-traumatic syndrome disorder), depression, and psychological fatigue, and overcome learned helplessness. In this case, the role of resilience is very important in the context of mental health experienced by students. Keywords: university student, resilience, mental health